2006
DOI: 10.1111/j.1365-2036.2006.02859.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased use of selective serotonin reuptake inhibitors in patients admitted with gastrointestinal haemorrhage: a multicentre retrospective analysis

Abstract: SUMMARY BackgroundSelective serotonin reuptake inhibitors (SSRIs) can adversely affect platelet function and impair haemostasis. Various bleeding complications have been reported in persons taking SSRIs including an increased risk of gastrointestinal haemorrhage (GIH).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 19 publications
2
57
1
2
Order By: Relevance
“…However, the conclusions of past studies varied; some concluded that the risk was not increased with combination use, 4,8,12,13) whereas others concluded that risk was increased [1][2][3][9][10][11][14][15][16][17] compared to use of SSRIs or NSAIDs alone.…”
Section: Discussionmentioning
confidence: 91%
“…However, the conclusions of past studies varied; some concluded that the risk was not increased with combination use, 4,8,12,13) whereas others concluded that risk was increased [1][2][3][9][10][11][14][15][16][17] compared to use of SSRIs or NSAIDs alone.…”
Section: Discussionmentioning
confidence: 91%
“…It has been reported that concomitant use of SSRIs and NSAIDs increases gastrointestinal bleeding (9,13,14,24,25). In addition, an interaction between SSRIs and corticosteroids has been also suggested (24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some clinical studies have recently reported the association of SSRI medication and gastrointestinal bleeding (9,10). Recent case-control studies (9,(11)(12)(13) and cohort studies (14) have shown that the risk of upper difficult to judge whether a symptom is induced by depression itself or by an adverse reaction to drugs. Gastrointestinal symptoms and endoscopic findings in psychiatric patients have been reported in western countries (15).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitant use of aspirin or other NSAIDs may potentiate the tendency to bleeding (Oyesanmi et al, 1999;Reeves et al, 2007). There is an increased risk of gastrointestinal haemorrhage (GIH) in patients prescribed SSRIs (Wessinger et al, 2006). SSRI use was more strongly associated with lower [OR (95% CI) 1.8 (1.2-2.8)] rather than upper [1.3 (0.83-1.9)] GIH.…”
Section: Other Dyscrasias Associated With Psychoactive Drug Treatmentmentioning
confidence: 99%